The Genome Sequence of Bluetongue Virus Type 2 from India: Evidence for Reassortment between Eastern and Western Topotype Field Strains - Maan, Narender S. (American Society for Microbiology, 2012)
Bluetongue virus type 2, isolated in India in 1982 (IND1982/01), was obtained from the Orbivirus Reference Collection at IAH Pirbright (http://www.reoviridae.org/dsRNA_virus_proteins/ReoID/btv-2.htm#IND1982/01). Full genome sequencing and phylogenetic analyses show that IND1982/01 is a reassortant virus containing genome segments derived from both eastern and western topotypes. These data will help to identify further reassortment events involving this or other virus lineages in the subcontinent.